Hubungan Pengetahuan dan Sikap Dengan Perilaku Hidup Bersih dan Sehat Rumah Tangga di Wilayah Kerja Puskesmas Tinggi Hari Kabupaten Lahat - Dewi Fortuna Anggraini; Nana Novariana; Tubagus Erwin (Malahayati Nursing Journal, 2026)
ABSTRACT According to the latest data from the World Health Organization (WHO) in 2022, approximately 2.2 million people in developing countries, especially children, die each year from various diseases caused by a lack of PHBS. Clean and Healthy Living Behavior (PHBS) at the household level is an effort to raise awareness among families, including all family members, so that they have the ability and willingness to practice PHBS in their daily lives. Low levels of PHBS implementation at the household level can lead to an increase in the incidence of environment-based diseases. The objective of this study is to determine the relationship between family knowledge and attitudes and the implementation of Clean and Healthy Living Behaviors (PHBS) in the Working Area of the Tinggi Hari Health Center, Lahat District, in 2025. This is a quantitative study with a cross-sectional design. The population consists of all household heads in the service area of the Tinggi Hari Health Center in Lahat District in 2025, totaling 92 households. The sampling technique used is total sampling with a sample size of 92 households. The instruments used are questionnaires, and the statistical test used is the chi-square test. The research results were obtained from 92 respondents, where the frequency distribution of knowledge showed that most respondents (57.6%) had insufficient knowledge, negative attitudes (59.8%), and poor PHBS (53.3%) out of 92 respondents. The chi-square test results showed a p-value for knowledge of 0.000 ≤ 0.05 and a p-value for attitude of 0.000 ≤ 0.05. The recommendation from this study is to provide health education and ongoing encouragement to households regarding PHBS, which will foster a positive attitude and promote the development of PHBS behavior. Keywords: Knowledge, Attitude, PHBS.  ABSTRAK Menurut World Health Organization (WHO) data terakhir tahun 2022 setiap tahunnya sekitar 2,2 juta orang di negara berkembang terutama anak meninggal dunia akibat berbagai penyakit yang disebabkan oleh kurangnya PHBS. Perilaku Hidup Bersih dan Sehat (PHBS) pada tatanan rumah tangga merupakan upaya dalam menyadarkan keluarga termasuk seluruh anggota keluarga agar memiliki kemampuan dan kemauan dalam melakukan praktek PHBS dalam kehidupan sehari-hari. Rendahnya tingkat penerapan PHBS di tingkat rumah tangga dapat menyebabkan meningkatnya kejadian penyakit berbasis lingkungan. Tujuan penelitian ini diketahui hubungan pengetahuan dan sikap keluarga dengan pelaksanaan Perilaku Hidup Bersih dan Sehat (PHBS) di Wilayah Kerja Puskesmas Tinggi Hari Kabupaten Lahat Tahun 2025. Jenis penelitian kuantitatif dengan rancangan penelitian cross sectional, populasi adalah seluruh Kepala Rumah Tangga di Wilayah Kerja Puskesmas Tinggi Hari Kabupaten Lahat 2025, sebanyak 92 KK, teknik sampling yang digunakan adalah total sampling dengan sampel 92 KK. Instrumen menggunakan kuesioner dan uji statistik yang digunakan  uji chi square. Hasil penelitian didapatkan dari 92 Responden dimana distribusi frekuensi Distribusi frekuensi pengetahuan didapatkan bahwa sebagian besar responden (57,6%) kurang, sikap (59,8%) negatif, PHBS (53,3%) kurang baik dari 92 responden. Hasil uji chi square pvalue pengetahuan 0,000 ≤ 0,05 dan pvalue sikap 0,000 ≤ 0,05. Saran penelitian ini pendidikan kesehatan dan memberikan dorongan yang bekelanjutan kepada tatanan rumah tangga terkait  PHBS maka akan menciptakan sebuah sikap positif sehingga tumbuhnya prilaku dalam melakukan PHBS. Kata Kunci: Pengetahuan, Sikap, PHBS.